The Economic Impact of Crime on Companies in Mexico, 2014-2024 - Valdez-Sánchez, David A.; Ortiz-Arango, Francisco (Journal of Posthumanism, 2025)
Criminal activity in Mexico has a significant economic impact on the business sector, characterized by being a multifactorial problem with institutional overtones. This work offers a framework for analyzing this phenomenon from a multidimensional perspective. The literature review revealed that existing studies generally approach the issue from a partial perspective, focusing on the crime-economic performance binomial, ignoring the institutional aspect. The methodology used is based on a review of the literature from the last ten years on crime and its economic effects, identifying relevant variables that characterize the crime phenomenon and its impact on the business sector in Mexico for the period 2014-2024. The work's fundamental contribution is to offer an alternative analysis framework through various indicators related to three essential aspects: the direct economic impacts that companies suffer due to crime, the institutional performance of the justice system in Mexico, and the incidence of crime in companies.